Pengembangan Sistem Pemetaan Status Mutu Air Sungai Berbasis Web Menggunakan Extreme Programming - Shofwatul Uyun (JISKA (Jurnal Informatika Sunan Kalijaga), 2020)
The high water pollution index causes a decrease in water quality so that it can interfere with the health of living things. In order to overcome this, the government has tried to monitor water quality whose results can be known by the community. However, information disclosure and ease of accessing information are felt to be lacking. This study aims to present information about the quality status of river water and its relatively up-to-date and easily accessed by the public online. The storet method is used to determine the status of river water quality with seven parameters: temperature, EC, TDS, pH, DO, BOD and E.coli. The features provided will be explained in the results and discussion presented in several UML diagrams. In order to get results that match user expectations, this system was developed with extreme programming system development methods.